Adult-onset hypophosphatemic osteomalacia associated with Sjogren syndrome: Clinical case report. Issue 13 (March 2017) - Shen, Guohua; Zhang, Yuwei; Hu, Shuang; Liu, Bin; Kuang, Anren
Abstract: Rationale: Hypophosphatemic osteomalacia (HO) is a metabolic bone disease, exhibiting different etiologies such as genetic mutation, tumor induction, dysimmunity, or renal disease. Sjogren's syndrome (SS) is a connective tissue disorder commonly involving exocrine glands; however kidney involvement is also encountered, leading to abnormal phosphorus metabolism, even HO. Patient concerns: A 47-year-old female patient presented progressively worsening pain in the chest wall, back and bilateral lower extremities as well as muscle weakness was referred to our department. Diagnoses, interventions and outcomes: Due to the laboratory test results, radiographic findings and pathologic results, she was diagnosed with adult-onset HO associated with SS. She was then treated with alkalinization, steroids, neutral phosphate, calcium supplements together with activated vitamin D. So far, she recovered uneventfully with relieved pain and increased serum phosphorus level. Lessons: HO may be secondary to renal tubular acidosis of SS patients, and it might be a diagnostic challenge when the kidney involvement in SS is latent and precede the typical sicca symptoms.